Synthesis and characterization of 11-vertex platinaborane compounds having nido-PtB10H12 and nido-Pt2B9H10 skeletons - Nie, Yong; Enders, Markus; Siebert, Walter (Polyhedron, 2012)
The reaction of closo-[B10H10]2− with [PtCl2(PPh3)2] in MeOH at reflux affords the B-methoxy substituted 11-vertex nido-platinaborane compound [(PPh3)2PtB10H10-8-H0.5(OCH3)0.5-10-(OCH3)] (1) and the known species [(PPh3)2PtB10H11-8-(OCH3)] (2) and 1,6-(PPh3)2B10H8 (3). The same reaction under solvothermal condition gives the partially degraded diplatinaborane [(PPh3)2(μ-PPh2)Pt2B9H7-3,9,11-(OMe)3] (4) with a novel nido-Pt2B9H10 skeleton. The new metallaborane compounds have been characterized by spectroscopic methods and single-crystal X-ray analyses. In particular, computational/theoretical chemistry supports the ultimate structural confirmation of 4. The structures of these metallaboranes exhibit interesting intra- and/or intermolecular C-H⋯O hydrogen bonding interactions.